Specification and verification of inter-component constraints in CTL. - Thang, Nguyen Truong (Software engineering notes.)
The most challenging issue of component-based software is about component composition. Current component specification, in addition to the syntactic level, is very limited in dealing with semantic constraints. Even so, only static aspects of components are specified. This paper gives a formal approach to make component specification more comprehensive by including component semantic. Fundamentally, the component semantic is expressed via the powerful temporal logic CTL. There are two semantic aspects in the paper, component dynamic behavior and consistency - namely a component does not violate some property in another when composed. Based on the proposed semantic, components can be efficiently cross-checked for their consistency by an incremental verification method - OIMC, even for many future component extensions.